Development of ICT-based interactive media using inquiry to improve mathematical communication - Samsul Bahri; Kms Muhammad Amin Fauzi; Waminton Rajagukguk (Himpunan Pengembang Kurikulum Indonesia, 2026)
Elementary school students' mathematical communication skills remain relatively low due to conventional instructional approaches and minimal use of technology-based interactive learning media. One-way explanations from teachers dominate the learning process, reducing students' ability to express mathematical ideas systematically in visual, symbolic, or written forms. This study aims to design and develop interactive learning media based on information and communication technology (ICT) using an inquiry learning model to improve students' mathematical communication skills. The inquiry model was chosen because it encourages exploration, active participation, and critical thinking. This study employs a Research and Development (RnD) approach using the ADDIE model, which comprises five stages: analysis, design, development, implementation, and evaluation. The research subjects included sixth-grade students, teachers, and material and media experts. Validity data were obtained from expert validation, practicality data from teacher and student questionnaires, and effectiveness data from pretest and posttest results. The results indicate that interactive learning media are highly valid, practical, and effective. This research suggests that the ADDIE-based development model can serve as a reference for designing adaptive, contextual, interactive media appropriate for the needs of elementary school students. Abstrak Kemampuan komunikasi matematis murid sekolah dasar masih tergolong rendah akibat pendekatan pembelajaran konvensional serta minimnya pemanfaatan media pembelajaran interaktif berbasis teknologi. Proses pembelajaran yang didominasi oleh penjelasan satu arah dari guru menyebabkan murid kurang mampu mengungkapkan ide matematis dalam bentuk visual, simbolik, maupun tulisan secara sistematis. Penelitian ini bertujuan merancang dan mengembangkan media pembelajaran interaktif berbasis teknologi informasi dan komunikasi (TIK) menggunakan model pembelajaran inkuiri untuk meningkatkan kemampuan komunikasi matematis murid. Model inkuiri dipilih karena mendorong eksplorasi, partisipasi aktif, dan berpikir kritis. Penelitian ini menggunakan pendekatan Research and Development (RnD) dengan model pengembangan ADDIE. Penelitian ini berfokus pada tahap pengembangan dan implementasi. Subjek penelitian mencakup murid kelas VI, guru, serta ahli materi dan media. Data validitas diperoleh dari validasi ahli, data kepraktisan dari angket guru dan murid, serta efektivitas dari hasil pretest dan posttest. Hasil penelitian menunjukkan media pembelajaran interaktif sangat valid, praktis, dan efektif. Implikasi penelitian ini adalah model pengembangan berbasis ADDIE dapat menjadi acuan untuk merancang media interaktif adaptif, kontekstual, serta sesuai kebutuhan murid sekolah dasar. Kata Kunci: komunikasi matematika; media interaktif; pembelajaran inkuiri; TIK